“I feel so small and big at the same time”—exploring body experience and binge eating disorder following inpatient treatment: a qualitative study - Olsen, Helene T.; Vangen, Sunniva B.; Stänicke, Line Indrevoll; Vrabel, KariAnne (Frontiers in Psychology, 2024)
Background: Limited research on Binge Eating Disorder (BED), low treatment rate and a lack of treatment rights, reflects a marginalised disorder in society and a treatment context.The aim of this study was to gain a deeper understanding of the psychopathology of BED, by exploring the patients' meaning related to the disorder and the role of the body in treatment of BED. Method: Qualitative methodology through reflexive thematic analysis.The data material is based on semi-structured in-depth interviews of six cis-gendered women who previously completed an inpatient treatment program for BED at a department for EDs and met the criteria for 307.51 Binge Eating Disorder in DSM-5. Results: The qualitative analysis rendered two meta themes with six themes and 12 subthemes. The first meta theme was "Relational challenges and feelings could not be talked about at home". The secondary meta theme was "Body contempt disturbs the experience of self and others" and the third was "Their body has not been a theme in previous treatment". This categorisation depicts a story of the disorder in terms of development, current condition, and experiences with prior treatment. Discussion: The findings indicate that shame and disgust are central play pivotal roles in the embodiment of BED, highlighting the significance of addressing one's relationship with their body for achieving recovery and to prevent an experienced repetition of the perceived rejection as a child.